Report on the Surface Phytoplankton Pigments measured during the JARE-34 Cruise to Syowa Station, Antarctica, November 1992 to March 1993 - Ishii, Masao; Suzuki, Toshikazu; Fukuchi, Mitsuo (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper